PENGARUH MARKET SIZE, KINERJA PERUSAHAAN, NILAI PERUSAHAAN, LEVERAGE, DAN KESEMPATAN BERTUMBUH TERHADAP STOCK RETURN - REFAN LEONARDO WISUTA; STELLA STELLA (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to test and analyze empirically the influence of market size, firm performance, firm value, leverage, and growth opportunity toward stock return. The object of this research is coal mine sector companies that listed in Indonesia Stock Exchange period 2010-2014. The purposive sampling is used as sampling technique, where 8 companies met the criteria and were analyzed using Eviews8 panel data regressions with random effect model to test the hypothesis. The result of this research shows firm performance and firm value influence stock return.While market size, leverage and growrh opportunity do not influence stock return.